Service Management as a Practice of Diakonia: A Theological Study on the Effectiveness of Equitable Service - Tesalonika Cindy Worang (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
The church's diaconal practice faces a crisis of effectiveness. The dominant model of charitable diakonia (almsgiving) has proven ineffective in addressing the root causes of poverty and structural injustice. Empirical studies show that this failure is often not due to a lack of resources, but rather a failure of strategic management and a narrow theological understanding of diaconal practice itself. This research argues that to respond to poverty effectively, the church requires a dual paradigmatic shift. First, a theological shift in service from charitable diakonia to transformative diakonia, grounded in Liberation Theology and Reformed social justice spirituality. Second, a conceptual shift in "management" from a secular concept to the theological practice of "Transformative Oikonomia", a prophetic stewardship rooted in scripture (Acts 6) and ecumenical frameworks (WCC). Using a qualitative literature review methodology, the author reconstructs a management model for effective and just ministry. In this model, "effectiveness" is redefined and measured not by logistical outputs, but by two theological pillars: (1) Relational Effectiveness, measured by the Theology of Hospitality (Pohl), focusing on the restoration of human dignity; and (2) Structural Effectiveness, measured by tangible contributions to the JPIC (Justice, Peace, and Integrity of Creation) agenda. This study concludes that the Transformative Oikonomia model liberates the church from the "charity trap" and enables a holistic fulfillment of the Missio Dei.